Metodološki i sadržajni aspekti znanstveno-istraživačkih radova objavljenih u Vjesniku bibliotekara Hrvatske : od 1998. do 2006. godine - Barbarić, Ana (Array, 2007)
One of the important issues in contemporary librarianship is the selection and use of appropriate research strategies which would provide that data collected in libraries are used for the optimum development of services. An analysis of the research strategies and subject content (topics) of articles published in Vjesnik bibliotekara Hrvatske in the period from 1998 to 2006 was made